To find the inverse of the function \( h(x) = 16x - 5 \) algebraically, follow these steps:
-
Replace \( h(x) \) with \( y \):
\[ y = 16x - 5 \]
-
Solve for \( x \) in terms of \( y \)**:
First, add 5 to both sides:
\[ y + 5 = 16x \]
Next, divide both sides by 16:
\[ x = \frac{y + 5}{16} \]
-
Swap \( x \) and \( y \) to express the inverse function:
\[ y = \frac{x + 5}{16} \]
-
Thus, the inverse function is:
\[ h^{-1}(x) = \frac{x + 5}{16} \]
So the inverse of the function \( h(x) = 16x - 5 \) is \( h^{-1}(x) = \frac{x + 5}{16} \).